Intravital imaging reveals p53-dependent cancer cell death induced by phototherapy via calcium signaling - Giorgi, Carlotta (Oncotarget, 2014)
One challenge in biology is signal transduction monitoring in a physiological context. Intravital imaging techniques are revolutionizing our understanding of tumor and host cell behaviors in the tumor environment. However, these deep tissue imaging techniques have not yet been adopted to investigate the second messenger calcium (Ca(2+)). In the present study, we established conditions that allow the in vivo detection of Ca(2+) signaling in three-dimensional tumor masses in mouse models. By combining intravital imaging and a skinfold chamber technique, we determined the ability of photodynamic cancer therapy to induce an increase in intracellular Ca(2+) concentrations and, consequently, an increase in cell death in a p53-dependent pathway.